PENGARUH MODEL PJBL BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SEKOLAH DASAR (JS (JURNAL SEKOLAH), 2025)
Abstract: This research is is based on the issue of students' low critical thinking skills, especially in science education. The aim of this study is to determine whether the PjBL learning model based on education for sustainable development can affect students' critical thinking skills. The method used in this study is a quasi-experimental design with a non-equivalent control group type, with a research population of 56 students. The sample consisted of 23 class IV A students (experimental group) and 23 class IV B students (control group). This research sample was selected using a purposive sampling technique. The data collection method used is a test. Based on data analysis, the PjBL model based on education for sustainable development has a significant influence on the critical thinking abilities of fourth grade elementary school students. This is based on the results of the independent t test showing a sig value of 0.000 indicating a sig value